Upaya Peningkatan Hasil Belajar Mata Pelajaran PAI Materi Jual Beli Melalui Penerapan Model Pembelajaran Problem Based Learning - Numan, Ah. Zanin; Rosyid, Adnan Miftakhur; Kustowo, Andi; Hakiman, Hakiman; Suluri, Suluri; Alwiyah, Noor (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2022)
The aim of this research is to determine the effectiveness of the problem best learning model in Islamic religious education subjects, buying and selling material. This research is classroom action research (PTK) conducted in class eleven (XI) of the Muhammadiyah 1 Sukoharjo Vocational School. The action study was carried out in two cycles, namely: planning, implementation, observation and reflection. The research results show that the problem-based learning model can improve students' abilities. The two cycles that have been stiffened show this improvement. Cycle I had 9 students in the complete category (28.12%), and Cycle II had 27 students in the complete category (84.37%). This proves that learning using the Problem Based Learning model has a positive impact on students in improving student learning outcomes in Islamic religious education subjects regarding buying and selling.